2019
DOI: 10.1021/acsaelm.9b00094
|View full text |Cite
|
Sign up to set email alerts
|

Analog Control of Retainable Resistance Multistates in HfO2 Resistive-Switching Random Access Memories (ReRAMs)

Abstract: Resistive-switching random access memory (ReRAM) technologies are nowadays a good candidate to overcome the bottleneck of Von Neumann architectures, taking advantage of their logic-in-memory capability and the ability to mimic biological synapse behavior. Although it has been proven that ReRAMs can memorize multibit information by the storage of multiple internal resistance states, the precise control of the multistates, their nonvolatility, and the cycle-to-cycle reliability are still open challenges. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 54 publications
1
21
0
2
Order By: Relevance
“…Modulation of a multi-level conduction state is a very essential aspect for the synaptic device to realize the high-density memory storage. To achieve multilevel memory states, gradual RESET has been controlled by V reset-stop , as shown in Figure 5 d. A similar approach has been shown in recent works on bilayer and tri-layer RRAM structures to obtain multi-state resistance by controlling V reset-stop [ 21 , 33 , 39 , 40 ]. Here, the positive RESET voltage was slowly increased to get a gradual RESET process in the HfO 2 /Al 2 O 3 /HfO 2 tri-layer RRAM device, which leads to multiple HRS.…”
Section: Resultsmentioning
confidence: 94%
“…Modulation of a multi-level conduction state is a very essential aspect for the synaptic device to realize the high-density memory storage. To achieve multilevel memory states, gradual RESET has been controlled by V reset-stop , as shown in Figure 5 d. A similar approach has been shown in recent works on bilayer and tri-layer RRAM structures to obtain multi-state resistance by controlling V reset-stop [ 21 , 33 , 39 , 40 ]. Here, the positive RESET voltage was slowly increased to get a gradual RESET process in the HfO 2 /Al 2 O 3 /HfO 2 tri-layer RRAM device, which leads to multiple HRS.…”
Section: Resultsmentioning
confidence: 94%
“…One can propose that the filament is weak near the Pt electrode, where the iterative breaking and forming of the CF occurs. This has been studied by Goux et al [28][29][30] and Giovinazzo et al [31] in Pt/HfO2/TiN and TiN/Ti/HfO2/Pt devices, respectively. Both studies concluded that the CF formed between the metal electrodes is weakened near the Pt.…”
Section: Discussionmentioning
confidence: 93%
“…Both studies concluded that the CF formed between the metal electrodes is weakened near the Pt. As this metal is chemically inert, it does not form oxides and thus, no oxygen vacancy-rich zone is generated near the interface [28][29][30][31][32][33]. Meanwhile, both TiN and Ti are good oxygen reservoirs, which generate vacancy-rich zones in the hafnium oxide near the HfO 2 /Ti or HfO 2 /TiN interface [14,28,29,34].…”
Section: Discussionmentioning
confidence: 99%
“…However, metal oxides are the most widely studied materials [9]. Among them, HfO x -based devices have been found to be highly scalable, CMOS compatible, and robust; and they are capable of ultrafast and low-energy consumption operation [10,11]. In lowtemperature applications, such as aerospace applications, the lack of low-cost, high-density, and endurable NVM has been a main limiting factor [12].…”
Section: Introductionmentioning
confidence: 99%